Longidtudinal assessment of performance in young male basketball players during a whole season - Olmedillas, H.; Calleja-Gonzalez, J.; Mjaanes, J.; Terrados, N. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Basketball is a sport with many complex demands that require a combination of fitness, skills, team strategies and motivational aspects. However key areas that are likely to play an important role in a basketball player´s success are muscular strength, fitness and body size. Purpose. The aim of the present study was to evaluate seasonal variation in anthropometric and physiological variables, and identify differences between the first and reserve team in elite young male basketball players. Methods. 15 top-level male players (Spanish team) guards (n=2), forwards (n=7), centers (n=6) (mean ± SD), age (14 years), height (189.1 ± 6.3 cm), body mass (74.6 ± 9.3 kg) participated in this study. The subjects were divided into two different categories: first team player (FT) (n=7) and reserve team player (RT) (n=8). All the players participated in the same training program (5 h per day). Four times during the season (September, December, March and June), each player performed various tests including countermovement jump (CMJ), Abalakov (ABK), horizontal jump (HJ), course Navette test (CN), and strength explosive arm test (SEAT). In addition anthropometrical data were recorded. Results. At the end of the training program the values were (Mean ± SD): [Height: 188.2 ± 5.4 vs. 190.6 ± 4.5 cm; 190.1 ± 7.6 vs. 192.1 ± 6.6 cm]; [Weight: 74.1 ± 12.0 vs. 77.8 ± 11.0 kg; 75.1 ± 6.0 vs. 81.6 ± 5.5 kg]; [Body fat: 8.2 ± 1.2 vs. 8.0 ± 1.1 %; 7.6 ± 0.6 vs. 7.5 ± 0.4 %]; [ABK: 39.0 ± 4.5 vs. 43.6 ± 4.4 cm; 38.8 ± 5.9 vs. 47.3 ± 6.0 cm]; [ HJ: 1.46 ± 0.3 vs. 1.76 ± 0.4 m; 1.38 ± 0.3 vs. 1.81 ± 0.4 m]; [CN: 9.8 ± 2.1 vs. 11.7 ± 2.0 paliers; 10.3 ± 2.4 vs. 12.0 ± 2.0 paliers]; [SEAT: 5.8 ± 0.8 vs. 6.5 ± 0.4 m; 5.5 ± 0.6 vs. 6.4 ± 1.0 m], FT and RT respectively. Pre and post training intra-group increased in both groups their height, max. speed, strength explosive arm, leg power and aerobic performance significantly (P<0.05). Conclusions. The progression of the both groups along the season was quite similar, with no significant differences in any anthropometric or physiological variables between them. At the end of the season and close to the international championship players presented the best results.